Comparison Of The Number Of Leukocytes, Lymphocytes, Monocytes and Neutrophils In Patients with Infectious and Non-Infectious Febriles: Perbandingan Jumlah Leukosit, Limfosit, Monosit dan Neutrofil pada Penderita Febris Infeksi dan Non Infeksi - Nadiyatul Husna Shofaroh; Syahrul Ardiansyah (Academia Open, 2024)
The examination parameters used to detect febris are leukocytes (WBC), erythrocytes (RBC), hemoglobin (Hb), hematocrit, and platelets. Leukocyte examination is very important to detect the cause of febris. The purpose of this study was to determine the comparison of the number of leukocytes, lymphocytes, monocytes, and neutrophils in patients with infectious and non-infectious febris. This study used a laboratory experimental research design, with quantitative methods. The research subjects were febris patients aged 0-5 years with a total of 60 patients. Data showing a significance value of p=0.000 (p<0.05) means that there is a comparison between the number of infectious and non-infectious febris leukocytes and the number of monocytes shows a significance value of p=0.003 (p<0.05) means that there is a comparison between the number of monocytes of infectious and non-infectious febris patients. While the number of lymphocytes showed a significance value of p=0.482 (p>0.05) meaning that there was no comparison between the number of lymphocytes with febris infection and non-infection, and the number of neutrophils showed a significance value of p=0.287 (p>0.05) meaning that there was no comparison between the number of neutrophils with febris infection and non-infection. Conclusion on the examination of the number of leukocytes, lymphocytes, monocytes, and neutrophils in infectious and non-infectious febris patients, there is a comparison in the number of leukocytes and monists between infectious and non-infectious febris patients. Highlight: Leukocyte exams crucial for febrile diagnosis. Variances in leukocyte and monocyte counts aid distinction. Unique cell count patterns reveal infection types. Keyword: Febris, Leukocytes, Lymphocytes, Monocytes, Neutrophils